(untitled) (MAUSAM, 1992)
The upper tropospheric energetics of the standing eddies in wave number domain during contrasting monsoon’ activity over India have been investigated. Two normal monsoon years (1970. 1971) and two drought monsoon years (1972, 1979) are considered for a comparative study, Energy equations of Saltzman (1957) are used to compute wave-wave Interaction and wave to zonal mean flow Interaction. Analysis of the results show that the standing eddies in the region of tropical easterlies (5°S-24 .2°N) have larger kinetic energy than those in the region of southern hemispheric, westerlies (24.2°S-5°S). Wave to zonal mean flow interaction of all waves (waves 1-15) Indicate that the standing eddies are a source of kinetic energy to zonal mean flow ID the region of easterlies and there sink of kinetic energy to zonal mean flow in the region of westerlies. In the region of easterlies planetary standing waves (waves 1-2) are the major kinetic energy source to other standing waves and wave-wave Interaction of all waves leads to positive Imbalance of kinetic energy during normal monsoon years (1970, 1971) and negative imbalance, of kinetic, energy during drought monsoon years (1972, 19 9). In the region of westerlies the imbalance of kinetic energy IS negative during normal monsoon years and positive during drought monsoon years.